Armillaria Root Rot (Also known as Mushroom Root Rot, Shoestring Root Rot, Honey Mushroom Rot) - Laura Sanagorski; Aaron Trulock; Jason A. Smith (EDIS, 2013)
Armillaria root rot is a disease that decays the root system of many common trees and shrubs. It is caused by several species of Armillaria, fungi that can be recognized by the clusters of yellow to honey-colored mushrooms that emerge during moist conditions. The disease is often lethal, and infected trees may have wilting branches, branch dieback, and stunted growth. Infected trees and shrubs should be removed and replaced with resistant species. This 4-page fact sheet was written by Laura Sanagorski, Aaron Trulock, and Jason Smith, and published by the UF Department of Environmental Horticulture, July 2013.